Apolipoproteins are associated with new MRI lesions and deep grey matter atrophy in clinically isolated syndromes. Issue 8 (27th January 2014) - Browne, Richard W; Weinstock-Guttman, Bianca; Horakova, Dana; Zivadinov, Robert; Bodziak, Mary Lou; Tamaño-Blanco, Miriam; Badgett, Darlene; Tyblova, Michaela; Vaneckova, Manuela; Seidl, Zdenek; Krasensky, Jan; Bergsland, Niels; et al.
Abstract : Objectives: There is increasing evidence that serum lipoprotein cholesterol biomarkers are associated with disease progression in clinically isolated syndromes (CIS). Apolipoproteins (Apo) are recognition ligands that mediate the physiological interactions of cholesterol-containing lipoproteins. The objective of this study was to investigate whether serum Apo levels are associated with CIS disease progression. Methods: ApoB, ApoAI, ApoAII, ApoE and lipoprotein (a) (Lpa) levels were measured in serum samples obtained prior to the start of treatment from 181 CIS patients (123 women, 58 men, 68% women; mean age: 28.1±SD 8.1 years). All patients were treated with intramuscular interferon-β as part of the prospective study. Clinical and MRI assessments were obtained at baseline, 6, 12 and 24 months after start of interferon-β treatment. Results: Greater ApoB levels were associated with increased number of new T2 lesions (p<0.001) and increased number of new or enlarging T2 lesions (p<0.001) over 2 years. Each 10 mg/dL of greater baseline ApoB is associated with a 16% increase in the number of new T2 lesions over 2 years. ApoAI, ApoAII, ApoE and Lpa were not associated with T2 lesions. Greater ApoE levels were associated with greater deep grey matter atrophy (partial correlation rp =−0.28, p<0.001). Each 1 mg/dL increment in ApoE levels was associated with a 1% increase in deep grey matter atrophy over 2 years. Conclusions: Serum ApoB levels are associated with new lesion accumulation whereas ApoE levels are associated with deep grey matter atrophy in high risk CIS patients treated with interferon β-1a.